Pengembangan Media Pembelajaran Terintegrasi Sejarah Matematika Berbasis Fitur Carousel Instagram pada Siswa SMP - Thahira Azzahra Yusuf; Juariah; Rikrik Nurdiansyah (Program Studi Pendidikan Matematika, FKIP Universitas Muslim Maros, 2026)
he rapid development of digital technology and social media presents opportunities for more interactive and relevant learning innovations, including in mathematics education. Instagram, widely used by adolescents, offers a carousel feature that enables concise and engaging visual content, while mathematics learning is often perceived as difficult when delivered through monotonous methods. Integrating the history of mathematics is considered effective in enhancing students’ motivation, conceptual understanding, and contextual learning experiences. This study aims to develop an Instagram carousel–based mathematics learning media integrated with the history of mathematics for the Pythagorean theorem in eighth-grade students. This Research and Development study employed the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. Research instruments included learning outcome tests, observation sheets, interviews, students’ needs analysis questionnaires, expert validation questionnaires, and practicality questionnaires. The results show that: (1) the developed media is “very valid” and “highly feasible”, with mean scores of 8.60 for technical aspects and 8.80 for material content; (2) The effectiveness of the media was